Strengthening the HR Capabilities – A Pathway to Strategic Success at SMEs of Punjab - Sharma, Manoj K.; Sharma, Sonali (Gyan Management Journal, 2023)
The Indian business sector is hyper-competitive and subject to the  complexities of its environment. Operating in a highly digitalized  and globalized world is not easy. However, by trying to strengthen  its capabilities, a firm can face the challenges of a borderless world  and other external pressures. Of all the internal factors, human  resource (HR) is supreme. It is a firm’s most valuable asset and a  major source for gaining competitive edge. Therefore, understanding  its role in a firm’s strategic success in imperative. The present study  attempted to determine the impact of HR practices on effective  strategy implementation of small and medium enterprises (SMEs)  of Punjab. Data was collected from 157 units through a self administered questionnaire. It was analyzed through mean scores,  frequencies and multiple regression analysis. Results revealed that six  of eight select HR practices had a statistically significant, strong and  positive impact on strategy implementation. HR remuneration and  rewards had the highest impact. The study concluded that adoption  of positive HR practices like attractive remuneration packages, better  training programmes, employee involvement and empowerment, etc.  enhanced effectiveness of strategic actions. The findings are to benefit  several parties and add Indian SME sector evidence to the domain.
Keywords: Human Resources; Strategy Implementation; Business Environment; Internal Environment; Competitive Advantage; SMEs